Reactive Oxygen Species, Antioxidant Agents, and DNA Damage in Developing Maize Mitochondria and Plastids - Tripathi, Diwaker; Nam, Andy; Oldenburg, Delene J.; Bendich, Arnold J. (Frontiers in Plant Science, 2020)
Maize shoot development progresses from nonpigmented meristematic cells at the base of the leaf to expanded and non-dividing green cells of the leaf blade. This transition is accompanied by the conversion of promitochondria and proplastids to their mature forms and massive fragmentation of both mitochondrial DNA (mtDNA) and plastid DNA (ptDNA), collectively as organellar DNA (orgDNA). We measured developmental changes in reactive oxygen species (ROS), which at high concentrations can lead to oxidative stress and DNA damage, as well as antioxidant agents and oxidative damage in orgDNA. Our plants were grown under normal, non-stressful conditions. Nonetheless, we found more oxidative damage in orgDNA from leaf than stalk tissues and higher levels of hydrogen peroxide, superoxide, and superoxide dismutase in leaf than stalk tissues and in light-grown compared to dark-grown leaves. In both mitochondria and plastids, activities of the antioxidant enzyme peroxidase were higher in stalk than in leaves and in dark-grown than light-grown leaves. In protoplasts, the amount of the small-molecule antioxidants, glutathione and ascorbic acid, and catalase activity were also higher in the stalk than in leaf tissue. The data suggest that the degree of oxidative stress in the organelles is lower in stalk than leaf and lower in dark than light growth conditions. We speculate that the damaged/fragmented orgDNA in leaves (but not the basal meristem) results from ROS signaling to the nucleus to stop delivering DNA repair proteins to mature organelles producing large amounts of ROS.